PENGARUH KOMPETENSI GURU TERHADAP MOTIVASI BELAJAR SISWA PADA MATA PELAJARAN KEWIRAUSAHAAN DI SMK KRISTEN 1 SURAKARTA - Veronika Ellyana; Mintasih Indriayu; Sudarno Sudarno (Department of Economics Education, Universitas Sebelas Maret, 2018)
The aim of this research is to find out the influence of the competence of the teacher to the motivation in learning of subject, especially in enterpreneurship subject. The kind of this research is survey. Population of this research are students of SMK Kristen 1 Surakarta in school year of 2015 / 2016. The respondents of this research are 115 as the sample. The data of this research was taken from the questionnaire given to the respondents. The method of data collection is document analysis through questionnaire. Validity of the data was taken from the result of the try out toward the 30 respondents. The technique of data analysis is linear regression. This research can be concluded that there is significant influence of the compentence of the teacher toward motivation of students in studying this subject. The result of this research is known from test T. Score of probability got in the test T is ( 0,000 ). It is smaller than 0,05. Thus, H0 is rejected, while Ha is accepted. The result of the Adjusted R Square is 0,511 (51,1%). It means that 51,1 % variable of student’s motivation in studying enterpreneurship is influenced by competence of a teacher.